2019
DOI: 10.1111/ssqu.12694
|View full text |Cite
|
Sign up to set email alerts
|

Melanated Millennials and the Politics of Black Hair

Abstract: Objective This research employs the phenotypic prototypicality framework to makes a connection between African‐American voters' perceptions of African‐American women candidates' appearances and candidate evaluations in contests with limited information. The primary focus is on the candidates' skin tone and hair texture. Methods The data consist of a convenience sample of 672 African‐American students from a Historically Black University in the Deep South. An experimental research design was employed to test wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 71 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…Based on participants' statements, African American girls continue to receive messages from family members, peers, and society that contribute to traumatic hair experiences and further perpetuate internalized racism based on the dominant culture's beauty standards and skin tone bias. However, as noted by (Orey and Zhang 2019), millennials are embracing natural hair and choosing to wear Afrocentric hairstyles. It is also worth exploring the experiences of the African diaspora outside of the US.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on participants' statements, African American girls continue to receive messages from family members, peers, and society that contribute to traumatic hair experiences and further perpetuate internalized racism based on the dominant culture's beauty standards and skin tone bias. However, as noted by (Orey and Zhang 2019), millennials are embracing natural hair and choosing to wear Afrocentric hairstyles. It is also worth exploring the experiences of the African diaspora outside of the US.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that bias exists regarding Black women's job performance based on hairstyle, demonstrating bias towards hairstyles considered professional, which often translates to less Afrocentric and more European. Given policies are often written to suit dominant culture standards, Orey and Zhang (2019) suggest that these stringent policies were in response to the Black Power Movement and an attempt to silence Black liberation.…”
Section: Significance Of Black Hairmentioning
confidence: 99%
See 2 more Smart Citations
“…Black women political elites in particular have markedly different experiences on the campaign trail and in the statehouse based on their skin color (Brown 2014). A recent study found that millennial voters believe that darker-skinned Black women candidates have more Afrocentric and progressive policy preferences than their lighter-skinned counterparts (Orey and Zhang 2019). Therefore, colorism also may impact candidate recruitment or viability (see also Dowe 2020).…”
mentioning
confidence: 99%